Senior education and the quality of life of women in different periods of old age - Beata Jurkiewicz; Edyta Barnaś; Małgorzata Kołpa (Kazimierz Wielki University, 2022)
Introduction. The current evolution in thinking considers the concern for the dignity of the elderly and their relationship with society. The intellectual and causal potential of older people, which was ignored so far, has also begun to be appreciated. The aim of the study was to assess the quality of life and its determinants in the group of women over 65 years of age (including age groups), using various forms of education for seniors. Material and methods. The study was conducted among women aged 65+ living in the Tarnów province (southern Poland): 205 educationally active seniors (group I) and 207 women who do not benefit from senior education (group II). The diagnostic survey method and standardized interview technique using the WHOQoL-AGE quality of life questionnaire were used. Results and conclusions. A higher level of quality of life was associated primarily with participation in senior education, lower age and better material status of the examined women. It is recommended to carry out activities promoting participation in various forms of senior education, especially in the two oldest age groups (old & oldest old).